Menakar Fungsi Lembaga Legislatif Di Indonesia - Iskatrinah Iskatrinah (Faculty of Law, Universitas Wijayakusuma, 2020)
The purpose of this research is to find out how the implementation of the ideal legislative function as a mandate from the 1945 Constitution which is then further regulated by its organic law. The research method used in this study is to use a normative legal research method, with the result that after the change in the 1945 Constitution of the Republic of Indonesia there is a shift in the wider function of the Central legislative body (DPR) and the Regional legislative body (DPRD), especially in the Central legislative body there was a transfer of power to form a law, which was previously under the authority of the President to become the power of the DPR, as stated in Article 20 paragraph (1) of the 1945 Republic of Indonesia State Constitution, namely the House of Representatives holds the power to form a law. The existence of community participation in the formation of laws is one form of community involvement in the life of the nation and state, because given the opportunity or space for people to participate in the formation of laws is a necessity in a democratic government system that establishes people as holders of sovereignty in the state. Because Indonesia as a country that adheres to a democratic system naturally opens up space for people to participate in politics, including participating in the formation of laws.Keywords: Function, Legislative, democracyÂ Â Abstrak. Tujuan dilakukannya penelitian ini adalah untuk mengetahui bagaimana pelaksanaan fungsi legislatif yang ideal sebagai amanat dari UUD 1945 yang kemudian diatur lebih lanjut dengan undang-undang organiknya. Metode penelitian yang digunakan dalam penelitian ini adalah menggunakan metode penelitian hukum normatif, dengan hasil bahwa pasca perubahan UUD Negara RI Tahun 1945 terdapat pergeseran fungsi yang lebih luas pada lembaga legislatif Pusat (DPR) maupun lembaga legislatif Daerah (DPRD), terutama di Lembaga legislatif Pusat terjadi perpindahan kekuasaan membentuk undang-undang, yang sebelumnya berada dalam kekuasaan Presiden menjadi kekuasaan DPR, sebagaimana dinyatakan dalam Pasal 20 ayat (1) UUD Negara RI Tahun 1945, yaitu Dewan Perwakilan Rakyat memegang kekuasaan membentuk undang-undang. Adanya Partisipasi masyarakat dalam pembentukan undang-undang merupakan salah satu bentuk keterlibatan masyarakat dalam kehidupan berbangsa dan bernegara, karena diberikan kesempatan atau ruang bagi masyarakat untuk berpatisipasi dalam pembentukan undang-undang merupakan sebuah keniscayaan dalam sistem pemerintahan demokrasi yang menetapkan rakyat sebagai pemegang kedaulatan dalam negara. Oleh karena Indonesia sebagai negara yang menganut sistem demokrasi wajar membuka ruang bagi masyarakat untuk berpatisipasi politik, termasuk berpatisipasi dalam pembentukan undang-undang.kata kunci : Fungsi, Legislatif, demokrasi